Rio Ibicuí: “rio de areia” durante a estiagem 2019-2020, na confluência com o rio Uruguai, Brasil - Sidnei Luís Bohn Gass; François Laurent; Roberto Verdum; Dieison Morozoli da Silva (Confins)
During the summer of 2019-2020, the state of Rio Grande do Sul was affected by a severe low flow, forcing 365 municipalities (three-quarters of those of the state) to declare an emergency. The objective of the study was to analyze a set of images, showing the hydromorphological forms of sedimentation in the area of confluence of the Ibicuí with Uruguay, visible due to the low water level. Satellite images from different periods have been used to show the hydrological dynamics that have arisen in the region. The analysis of the images allowed us to consider that the landscape dynamics of the selected area, influenced by its flat topography, is under the strong dependence of meteorological events, associated with the variability of the subtropical climate in the south of Brazil.